Hitler's Generals - Brett-Smith, Richard, 1923- (London Osprey Publishing Ltd., 1976)
Includes chapters on the Luftwaffe and the Waffen SS.
Include Index, Bibliography, Maps, Appendix and Illustration
Keywords: World War (1939-1945) -- Germany -- Germany. Heer